UMAR BIN KHATTAB : Tinjauan Sejarah Terhadap Dinamika Pemerintahan - Maruli Tumangger (Universitas Islam Negeri Sumatera Utara, 2023)
Umar bin Khattab was the second caliph in the history of Islamic rule. Lots of progress was achieved during the period of his caliphate. This article was compiled in order to explain from a historical perspective the dynamics of government that occurred during the caliphate of Umar bin Khattab. This article begins with an explanation of the process of appointing Umar bin Khattab and an explanation of the government structure that was built during his time along with an explanation of the duties and functions of each structure. With this research it was found that the government structure that was built during the time of Umar bin Khattab was well structured at that time. This article then discusses the dynamics of the government at that time which consists of an explanation of the socio-political, religious, intellectual and economic dynamics